Development of high-strength deep-well pump rods for oil production based on innovative metallurgical technologies - Azimova, Lala; Shukyurov, Rahim; Mirbabayeva, Naila (My University, 2025)
In the world, including the Republic of Azerbaijan, oil production from 75-85% of wells is carried out by deep-well pumps. A deep-well pump located at the bottom of the well is connected to a pumping unit at the wellhead with rods. The pump brings oil to the surface of the wells either due to the reciprocating motion of the rod string or due to its rotation in one direction. In the first case, the rod string operates under a repetitive, variable tensile load with an asymmetric cycle, and in the second- under a torsional load. The chemical composition and design of the rods used in both cases are the same. Pump rods (Fig. 1) are long (8 m long) products of small diameter (16-25 mm) and are considered the weakest link in oil production by pumping. Shutdown of oil wells in most cases occurs as a result of rod breakage. Therefore, the level of oil production by this method depends on the strength and reliability of the pump rod. The aim of the research work is to obtain high-strength rods for deep-well pumps by using innovative metallurgical technologies. This is a pressing scientific and technical problem.
Keywords: sucker rod; steel; thermomechanical treatment; hardenability